(We're working over $\mathcal{Ab}$)

Essentially, I need to show that if the following sequence is exact:$$0\rightarrow A\stackrel{f}{\longrightarrow}B\stackrel{g}{\longrightarrow} C \rightarrow0$$ then so is this sequence: $$0\rightarrow \text{Hom}(C,X)\xrightarrow{g^*=\ \text{$-\ \circ\ g$}} \text{Hom}(B,X)\xrightarrow{\text{$f^*=\ -\ \circ\ f$}} \text{Hom}(A,X)$$

So, it's straightforward to show the exactness at $\text{Hom}(C,X)$ i.e. the injectivity of $g^*$, since $g$ is an epimorphism

$$h \circ g=g^*(h) = g^*(k) = k \circ g \implies h=k$$

Now, to show $\ker f^* = \text{im } g^*$

Since, we have $f^* \circ g^*= (g \circ f)^* = 0^*=0 \implies \ker f^* \supseteq \text{im } g^*$

We now have to show that if $f^*(h) =h \circ f = 0 \implies \exists\ k$ such that $h=g^*(k) = k \circ g$

So, we have $$h(f(x))=0\ \ \forall x \in A \implies h(\text{im }f)=0 \implies h(\ker g)=0$$ I also have that $C\cong B/\ker g$, and I'll denote this isomorphism by $\phi$

So, we define $k \in \text{Hom}(C,X)$ as $k(x) = h(\phi(x))$. And since, $\phi(x)=b + k$, where $b \notin \ker g,\ k \in \ker g$. Then simply, $k(x) = h(b)$

Since $\phi$ was an isomorpshim, $h$ is completely defined by $k$ as well, and since $x \in C = \text{im }g \implies \exists\ y\in B\ \colon x=g(y) \implies h = k \circ g $

Therefore, $\ker f^* \subseteq \text{im } g^*$

I have a feeling that I've gone wrong somwhere, can I get some assistance accordingly?


1 Answer 1


One inclusion, namely $\ker f^*\supseteq\operatorname{im} g^*$ is obvious, because $f^*\circ g^*=(g\circ f)^*=0^*=0$. Your argument is correct.

Now let $h\in\ker f^*$, which means $f^*(h)=h\circ f=0$. This is equivalent to $\operatorname{im}f\subseteq\ker h$ and, by exactness of the original sequence, $\ker g\subseteq\ker h$.

By the homomorphism theorems, $h\colon B\to X$ induces a homomorphism $\bar{h}\colon B/\ker g\to X$ such that $h=\bar{h}\circ\pi$, where $\pi\colon B\to B/\ker g$ is the canonical map.

By assumption, $g$ induces an isomorphism $\bar{g}\colon B/\ker g\to C$ such that $g=\bar{g}\circ \pi$. Consider $k=\bar{h}\circ\bar{g}^{-1}\colon C\to X$ and compute $$ g^*(k)=k\circ g $$ Your idea is good, but can be made more precise, as you see.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .